Dexmedetomidine improves acute stress‐induced liver injury in rats by regulating MKP‐1, inhibiting NF‐κB pathway and cell apoptosis. Issue 8 (7th January 2019) - Sha, Jichen; Feng, Xiujing; Chen, Yongping; Zhang, Huayun; Li, Bei; Hu, Xueyuan; Fan, Honggang
Abstract: Acute stress is a frequent and unpredictable disease for many animals. Stress is widely considered to affect liver function. However, the underlying mechanism by which dexmedetomidine (DEX) attenuates acute stress‐induced liver injury in rats remains unclear. In this study, we used forced swimming for 15 min and acute 3‐hr restraint stress model. Behavioral tests and changes in norepinephrine levels confirmed the successful establishment of the acute stress model. Acute stress‐induced liver injury, evidenced by hematoxylin and eosin‐stained pathological sections and increased serum aminotransferase and aspartate aminotransferase levels, was reduced in DEX‐treated livers. Reactive oxygen species and oxidative stress levels were dramatically decreased with DEX treatment compared with acute stress‐induced liver injury. DEX significantly reduced acute stress‐induced liver inflammation and apoptosis, as assessed by terminal deoxynucleotidyl transferase dUTP nick‐end labeling staining and inflammation and apoptosis‐related protein levels. DEX treatment also effectively inhibited acute stress‐induced c‐Jun N‐terminal kinase (JNK), P38, and BAD signaling pathway activation, and significantly induced MKP‐1 activation. Thus, DEX has a protective effect on acute‐stress‐induced liver injury by reducing inflammation and apoptosis, which suggests a potential clinical application for DEX in stress syndrome. Abstract : DEX has a protective effect on acute‐stress‐induced liver injury by reducing inflammation and apoptosis, which suggests a potential clinical application for DEX in stress syndrome. DEX may be useful for treating stress syndrome in human or veterinary patients. Further studies are needed to elucidate the pharmacologic effects of DEX in other tissues that are damaged by acute stress.